POTENSI Epigallocatechin-3-gallate TERMIKROENKAPSULASI NANOLIPOSOME SEBAGAI UPAYA PENCEGAHAN PENYAKIT PARKINSON - Putri, Ritma Ratri Ayunda; Almira, Amanda Belva; Azizah, Maghfira Rahma (Essence of Scientific Medical Journal; Vol 20 No 2 (2022): Volume 20 No. 2 (Juli - Desember 2022) Essential: Essence of Scientific Medical Journal, 2023)
ABSTRACT   Background: Parkinson’s is a progressive neurodegenerative disease characterized by loss of dopamine neurons in the substantia nigra pars compacta. Nowadays, there are several management agents to treat parkinson disease, in fact, these can only treat the symptoms not the trigger factor. Epigallocatechin-3-gallate (EGCG) is the best-known bioactive component of green tea (e.g., Camellia sinensis ) that has the potential in preventing Parkinson’s disease (PD). To optimize the antioxidant effect, EGCG must be encapsulated with nanoliposome as a delivery system to protect its stability and bioactivity. Objective: To determine the effectiveness of Epigallocatechin-3-gallate with nanoliposome microencapsulated in preventing parkinson disease. Method: This review utilized search engines such as Pubmed and Sciencedirect to search for articles. The main keywords used in this searching process were “ Epigallocatechin-3-gallate ”, “ Prevention ”, and “ Parkinson disease ” using boolean operators to get structured a specific search result. We found 10 articles that fulfill the inclusion criteria. The inclusion criteria are based on PICOS framework containing five dimensions, those are populations (parkinson patient, cell culture models of parkinson, animal models of parkinson’s disease), intervention ( Epigallocatechin-3-gallate or EGCG), comparison (control), outcome (improvement of parkinson’s symptoms or decreased progressivity of parkinson disease, and study design (experimental). Result and Discussion: EGCG is proven to be safe and effective in preventing parkinson disease. Another study stated that the use of nanoliposome as a microencapsulation agent proved effective in maintaining the viability of EGCG. Conclusion: EGCG with nanoliposome microencapsulated proved effective in preventing parkinson disease.   Keywords: E pigallocatechin-3- gallate, N anoliposome, N europrotective, P arkinson D isease